Maternal homework approach and adolescents’ academic skills: The mediating role of task values - Silinskas, Gintautas; Viljaranta, Jaana; Poikkeus, Anna-Maija; Lerkkanen, Marja-Kristiina (Frontiers in Education, 2022)
The present study investigated the mediating role of the task values between the types of maternal homework approach (perceptions of their child’s autonomy or direct involvement) and adolescents’ academic skills. Data were utilized from 995 mother–child dyads followed across Grades 6, 7, and 9. At each time-point, mothers answered questionnaires on the types of their homework approach, adolescents answered questionnaires about their task values for math and Finnish, and adolescents’ skills in math (arithmetic and multiplication) and reading (reading fluency and reading comprehension) were tested. Separate longitudinal structural equation models were estimated for math and for reading. The results showed, first, that maternal perceptions of their adolescents’ autonomy positively predicted adolescents’ task values but did not predict skills. Second, maternal direct involvement in homework completion negatively predicted adolescents’ math and reading skills but did not predict task values. Finally, concerning the effect of task values between homework approach and skills, task values in Grade 7 played a role in the associations between perceptions of autonomy (but not direct involvement) in Grade 6 and adolescents’ skills in Grade 9. Overall, the present study highlights the importance of student autonomy with regard to homework in promoting adolescents’ task values as well as the role of adolescents’ task values in the associations between maternal perceptions of autonomy and the development of adolescents’ math and reading skills.